Key issues for the design and development of mobile commerce services and applications - Schizas, Christos N.; Pitsillides, Andreas; Mavromoustakos, Stephanos M.; Samaras, George; Leonidou, Costantinos; Chrysostomou, Chrysostomos; Andreou, Andreas S. (My University, 2005)
This paper suggests a new approach for developing m-commerce services and applications based on a scheme that divides m-applications into directory- and transaction-oriented classes, identifies mobile user requirements, and takes into consideration the constraints of current technologies for mobile and wireless computing. The efficacy of the proposed approach in a real scenario is discussed. Copyright © 2005 Inderscience Enterprises Ltd.
Keywords: m-commerce; Mobile applications; Cyprus telecommunication authority; Mobile services; Mobile user requirements; Quality